(untitled) (Biological Sciences - PJSIR, 2023)
Soil productivity and fertility tends to decline if the nutrient requirement of an intensive cropping system is not managed prudently. Long term use of sole chemical fertilizers exhausts the indigenous pools of carbon and non-applied nutrients. It was a two factorial quadruplicated in randomized complete block design (RCBD) field experiment. Factor-1 treatments were cultivation of sole sugarcane and sugar beet, along with intercropping of both. Factor-2 included organic amendments, viz., farmyard manure (FM), press mud (PM) and compost (CP) used at (10 t/ha) with fertilizer rates (100, 250 Kg/ha) each of N-P205- K20. Crop yield attributes and sugar yield data gave non-significantly difference between intercrops and cultivation of sugarcane and sugar beet sole, although there were slightly higher values for planting sole. Higher dose of NPK viz., 250 Kg/ha combined with FM gave better response regarding crop and sugar production and maximum economic returns. Sugarcane sugar beet intercropping proved financially higher to outdatedfarming system through integrated plant nutrient management. Among organic amendments, CP performed lower, while FM rendered upper values of crop and sugar production at both rates of fertilizer.